Effects of Confinement on Interaction Diagrams of Square Reinforced Concrete Columns - Tavio Tavio; Iman Wimbadi; Ardiansyah Kusuma Negara; Recky Tirtajaya (Civil Engineering Dimension, 2009)
To prevent brittle failure, the design of a structural column in a seismic-resistant building is of important consideration, particularly in terms of confinement. In the recent building code, the need of closely-spaced stirrups in a structural member, such as column becomes compulsory due to the ductility and strength considerations. However, the design is based on the simplified block stress of unconfined concrete, and does not account for the strength gain due to the presence of confinement. To investigate the effects of lateral confinement on the column capacity, an analytical study is carried out. Both the strength gain in concrete core and the loss of strength in the cover are considered in the analytical models to exhibit the remaining strength gain after the mobilization of strength gain in the core concrete to compensate the loss of strength in the concrete cover. There are six key parameters primarily influence the effectiveness of lateral confinement. The most influencing parameter is found to be the spacing of transverse steel. The presence of closely-spaced lateral confinement significantly increases the magnitude of stress-strain curve of concrete. This increase expands the interaction diagram of the column particularly when it is in the compression-controlled region (for lower-story columns when axial load dominates the behavior).